2003
DOI: 10.1111/1467-9280.24441
|View full text |Cite
|
Sign up to set email alerts
|

The “Ticktock” of Our Internal Clock

Abstract: The phenomenon commonly known as subjective accenting refers to the fact that identical sound events within purely isochronous sequences are perceived as unequal. Although subjective accenting has been extensively explored using behavioral methods, no physiological evidence has ever been provided for it. In the present study, we tested the notion that these perceived irregularities are related to the dynamic deployment of attention. We disrupted listeners' expectancies in different positions of auditory equito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
134
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(160 citation statements)
references
References 33 publications
(43 reference statements)
11
134
1
4
Order By: Relevance
“…Support for the task-relatedness of this component comes from various studies which interpret the late positive component as a reflection of task-specificity and task-sensitivity (cf. Picton, 1992;Coulson, King, & Kutas, 1998;Knaus et al, 2007;Magne et al, 2007;Domahs et al, 2008Domahs et al, , 2012Domahs, Kehrein, Knaus, Wiese, & Schlesewsky, 2009;Schmidt-Kassow & Kotz, 2009a, b;Marie et al, 2011). In general, a comparison between grand average ERP curves for correct and incorrect conditions reveals that stress violations in stems A2 and B evoke less pronounced neural responses than in stems A1 and C; in A2 it is absent, while in stem type B it is found in parietal regions only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for the task-relatedness of this component comes from various studies which interpret the late positive component as a reflection of task-specificity and task-sensitivity (cf. Picton, 1992;Coulson, King, & Kutas, 1998;Knaus et al, 2007;Magne et al, 2007;Domahs et al, 2008Domahs et al, , 2012Domahs, Kehrein, Knaus, Wiese, & Schlesewsky, 2009;Schmidt-Kassow & Kotz, 2009a, b;Marie et al, 2011). In general, a comparison between grand average ERP curves for correct and incorrect conditions reveals that stress violations in stems A2 and B evoke less pronounced neural responses than in stems A1 and C; in A2 it is absent, while in stem type B it is found in parietal regions only.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of evidence that would uncontroversially point to one or the other foot type, both structures have been postulated on purely theoretical grounds. An iambic foot has been proposed by Halle and Vergnaud (1987), Melvold (1990), Alderete (1995), and Crosswhite (2001), whereas a trochaic foot has been assumed by Idsardi (1992), Halle and Idsardi (1995), and Halle (1997).…”
Section: Russian Stress -Basic Factsmentioning
confidence: 99%
“…Research has shown that we tend to interpret rhythm in a metrical context (Honing, 2012)-that is, in relation to an organization of the pulse level. Even when we are presented with isochronous sequences of equivalent sounding events, we do not process them as equal, due to the subjective accenting (Brochard et al, 2003). We perceive meter when certain beats in a pulse are perceived as accented in a regularly repeating pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Metrical patterns need not be consistently emphasized with relatively strong and weak accents in order to be perceived (London, 2004) just as tonally stable pitches do not need to be emphasized in order for a tonal hierarchy to be understood (Larson, 1997). In fact, much evidence points to listeners imposing hierarchies with very little musical context in both metric (Brochard et al, 2003;Desain & Honing, 2003;Palmer & Krumhansl, 1990) and tonal domains (Cuddy & Badertscher, 1987;Smith & Schmuckler, 2004).…”
mentioning
confidence: 99%